Futures and Foresight in Participatory Planning. Exploring the images of the future in communities of the transforming Indonesian capital city – Nusantara - Jones-Wilenius, Ana (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2024)
The Indonesian government is relocating its capital city Jakarta to East Kalimantan in the Island of Borneo. The development of this new national capital best known as Nusantara offers two competing narratives, one of a green and smart “World City for All” (OIKN), and another one of adverse in-situ rural transformation and construction impacts. From a futures perspective, this major change prompts several questions about the images and attitudes that exist in the mind of the communities of people who will create the new social fabric of the city. Central to this is the understanding of long-term implications of those images, how they get manifested in planning, and what new opportunities will emerge from this major rural-urban transformation. Using futures and foresight methods and tools, our task has been to explore the attitudes and perceptions held by local and migrant residents towards the new capital city. We collected, processed and analysed the perceptions and expectations of six different groups of residents from the Argo Mulyo Village in the (Sepaku District) and from other surrounding villages. The groups were invited to take part on a series of futures workshops designed to be participatory. This Futures and Foresight in Participatory Urban Planning report informs on the foresight process steps that were conducted and the results from the workshops activities. The report been produced in the context of the Co-Creation project Foresight for Resilient Cities (FoReCi), a cross-disciplinary effort between the Centre for East Asian Studies (CEAS) and the Finland Futures Research Centre (FFRC) at the University of Turku.